2013
DOI: 10.1007/s10815-013-9979-z
|View full text |Cite
|
Sign up to set email alerts
|

Association study between FSHR Ala307Thr and Ser680Asn variants and polycystic ovary syndrome (PCOS) in Northern Chinese Han women

Abstract: Background Polycystic ovary syndrome (PCOS) is a common complex genetic endocrinopathy. It has high heritability, and twin studies indicate that it is a complex polygenic disorder. Searching for major genes of PCOS is crucial to clarify its molecular pathogenesis. A previous genome-wide association study in Chinese women with PCOS identified a region on chromosome 2p16.3 that encodes the follicle-stimulating hormone receptor (FSHR) genes as a reproducible PCOS susceptibility locus. In the present study, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
3
23
1
Order By: Relevance
“…We analyzed the association of PCOS with 11 SNPs from LHCGR and FSHR previously tested for their association with PCOS in European [18][19][20]25], and non-European [17,[26][27][28][29] populations. This case-control sample included 203 women with PCOS and 211 age-and ethnically-matched (Bahraini Arab) control women.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the association of PCOS with 11 SNPs from LHCGR and FSHR previously tested for their association with PCOS in European [18][19][20]25], and non-European [17,[26][27][28][29] populations. This case-control sample included 203 women with PCOS and 211 age-and ethnically-matched (Bahraini Arab) control women.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Asn680Ser polymorhism of FSHR was reported to be related to the levels of FSH and PRL while other PCOS-associated endocrine hormones were not [29]. In another study by Fu et al, this SNP was found to be associated with high levels of FSH and low E2 levels [12].…”
Section: Discussionmentioning
confidence: 97%
“…Gu et al revealed that the Asn680 Ser of FSHR was associated with PCOS in Korean women [9]. On the otherhand, Fu et al reported that the Asn680Ser polymorphism of FSHR was not a causative factor of PCOS in Chinese women [12]. All of these studies were conducted on different ethnic groups from different geographic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these SNPs result in amino acid substitutions and, therefore, might affect protein expression or function [29, 34]. The associations have not always been found, perhaps due to population differences and a limited cohort size and a limited number of genetic variants examined [30, 35]. …”
Section: Coding Sequence Variants In Fshr Lhcgr and Insr Associated mentioning
confidence: 99%